THE USE OF TABOO WORDS IN PAK DARTO CHARACTER IN TENDANGAN DARI LANGIT MOVIE - CHOTIMAH, CHUSNUL (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: taboo words, types, purposes, Tendangan Dari Langit movie, PakDarto.Communication is very important in our life because people can understand each other through communication. Taboo word is one of linguistic phenomena which exist in most languages because every member of society has different way to express his thoughts in language. It is interesting to analyze the various kinds of taboo words which are expressed by men character in the movie Tendangan dari Langit. This study is aimed at describing taboo word phenomena in Tendangan Dari Langit movie. There are two research problems to be solved, those are to find out the types and the purposes of Javanese taboo words used by Pak Darto in Tendangan Dari Langit movie.In this research, the writer used qualitative method with document or content analysis. The writer only analyzed the Javanese taboo words that were spoken by Pak Darto to describe the analysis on types and purposes of taboo words. In analyzing the type of Javanese taboo words, the writer used Wardhaugh’s (2006) theory, while for analyzing the purposes of Javanese taboo words, the writer used Liedlich’s (1973) theory.From the result of analysis, the writer found 10 utterances containing Javanese taboo words by Pak Darto. The writer found that Pak Darto used 5 types of taboo words to express his feelings, they are one’s mother in law, bodily function/human genitals term, death, excretion and creating game/animal. Furthermore, Pak Darto only had 4 purposes in using the taboo words, namely to discredit, to provoke violent confrontation, to an endearment and to provide catharsis.The writer suggests English Department students to conduct the research on taboo language using other theories such as Hughes’s or Holmes’s theory. She also suggests the next researcher to learn more about Javanese taboo language in daily conversation, Javanese poetry or incantation.